The EU law on cryptoassets : a guide to European fintech regulation / Dirk Zetzsche, University of Luxembourg, Jannik Woxholth, University of Luxembourg. - Zetzsche, Dirk; Woxholth, Jannik (Cambridge University Press, 2025)
This book provides a comprehensive guide to EU regulation of crypto-assets and FinTech regulation more broadly. The authors explain the need for regulation in an accessible manner and against the background of the instances now dubbed the 'Crypto Winter', when millions of crypto investors lost billions of value due to technical malfunctions, misconduct, and fraud. They combine an in-depth perspective on the bespoke regulations of crypto-assets provided in the EU's Markets in Crypto-Assets Regulation (MiCA) and Pilot Regulation with the revised EU's AML/CTF legislation, operational risk regulation (DORA), and private law. They conclude by analysing how the combined new EU financial regulation addresses the causes of the Crypto Winter, and which risks remain despite the plethora of new policy action. Co-written by a world-leading FinTech expert, the book will be a go-to source for researchers and practitioners and a crucial guide for those navigating the field of crypto-assets.